Comparative analysis of two techniques for detection and segmentation of moving bodies - Filitto, Danilo [UNESP]; Hasegawa, Julio Kiyoshi [UNESP]; Polidorio, Airton Marco [UNESP]; Flores, Franklin Cesar [UNESP] (Ieee, 2013)
This paper makes a comparative analysis of results produced by the application of two techniques for the detection and segmentation of bodies in motion captured in images sequence, namely: 1) technique based on the temporal average of the values of each pixel recorded in N consecutive image frames and, 2) technique based on historical values associated with pixels recorded in different frames of an image sequence.